STUDI KOMPARATIF PENGUASAAN KONSEP ULUMUL QURâAN DALAM PEMBELAJARAN YANG MENGGUNAKAN FULL E-LEARNING DAN BLENDED E-LEARNING - Umar, Umar (JURNAL TAPIS, 2013)
This study aims to determine how differences in student mastery of the material concept Ulumul Quran and how students respond after getting lessons with full e-learning (e-learning entirely) and blended e-learning (a combination of e-learning and face to face). The research method used was experimental real (true experiment) randomize design with the pretest-posttest control group performed at STAIN Jurai Siwo Metro. Analysis of test data performed by the t-test statistical techniques to look at the difference in mean score of the pretest and posttest mastery of concepts both study groups, and quantitative analysis of Likert scale on student responses. Posttest grades shows that students classroom full of e-learning has increased mastery of the concept of a higher grade than students of blended e-learning. However, the results of statistical calculations apparently increased mastery of concepts between experimental and control classes were not significantly different. From the results of different test average posttest study both classes, obtained Sig. (2-tailed) sebesar 0,083. The point is 0,083 > 0,05. Tcount is located in the reception area H0, proving that there is no significant difference between the mean posttest classroom full of e-learning and blended e-learning classes. When viewed an average of N-Gain between experimental class with a class that controls 54% and 47% experienced an increase in the medium category.Â Keywords: Comparative, Ulumul Quran full e-learning and blended e-learning.